Understanding employee innovative behavior and thriving at work: A Chinese perspective - Sidra Riaz; Yusen Xu; Shahid Hussain (Administrative Sciences, 2018)
Drawing from the tenets of social cognitive theory, the present study examined the effect of thriving at work on innovation behavior via organizational support of innovation. The data were collected at three points in time from 402 participants occupying a variety of positions in Chinese organizations. Structural equation modeling and multilevel regression analysis results demonstrated that employees' thriving was positively related to organizational support of innovation, which in turn was positively related to innovative behavior. In addition, moderated mediation results demonstrated that employee external contacts strengthened the relationship between organizational support of innovation and innovative behavior, and enhanced the positive effects of thriving. Our results deepen and go beyond previous research on thriving at work. The theoretical and practical implications of these findings are discussed.
Keywords: 350; thriving at work; organizational support of innovation; innovative work behavior; external work contacts